2005
DOI: 10.1093/hmg/ddi215
|View full text |Cite
|
Sign up to set email alerts
|

Loss of function mutations in the gene encoding Omi/HtrA2 in Parkinson's disease

Abstract: Recently targeted disruption of Omi/HtrA2 has been found to cause neurodegeneration and a parkinsonian phenotype in mice. Using a candidate gene approach, we performed a mutation screening of the Omi/HtrA2 gene in German Parkinson's disease (PD) patients. In four patients, we identified a novel heterozygous G399S mutation, which was absent in healthy controls. Moreover, we identified a novel A141S polymorphism that was associated with PD (P<0.05). Both mutations resulted in defective activation of the protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
382
1
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(400 citation statements)
references
References 30 publications
7
382
1
10
Order By: Relevance
“…7 Missense mutations in the gene coding for Omi were reported to be associated with Parkinson's disease (PD). 8 In agreement with these findings, accumulation of Omi was found in neuronal and glial inclusions in brains with a-synucleinopathies, 9 as well as in Lewy bodies. 8 Omi knockout (KO) mice suffered the loss of a population of neurons in the striatum, which resulted in a neurodegenerative disorder with a PD phenotype.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…7 Missense mutations in the gene coding for Omi were reported to be associated with Parkinson's disease (PD). 8 In agreement with these findings, accumulation of Omi was found in neuronal and glial inclusions in brains with a-synucleinopathies, 9 as well as in Lewy bodies. 8 Omi knockout (KO) mice suffered the loss of a population of neurons in the striatum, which resulted in a neurodegenerative disorder with a PD phenotype.…”
supporting
confidence: 75%
“…8 In agreement with these findings, accumulation of Omi was found in neuronal and glial inclusions in brains with a-synucleinopathies, 9 as well as in Lewy bodies. 8 Omi knockout (KO) mice suffered the loss of a population of neurons in the striatum, which resulted in a neurodegenerative disorder with a PD phenotype. These mice died within 30 days after birth, similarly to mnd2 mice.…”
supporting
confidence: 75%
“…To date (2010), 11 genes and an additional 3 genetic loci have been associated with PD [168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184]; two additional loci await to be confirmed [185,186]. The PD genes and loci are described in Table 4.…”
Section: Genes and Loci In Familial Pdmentioning
confidence: 99%
“…A German study screened PD cases for mutations in the Omi/HtrA2 gene because Omi/HtrA2 is associated with a parkinsonian phenotype in mice [182]. One heterozygous mutation was detected in four of 518 PD cases, and in vitro studies indicated that the mutation resulted in impaired protein function.…”
Section: Park13mentioning
confidence: 99%
“…Moreover, both Omi-knockout mice and mnd2 (motor neuron degeneration 2) mice, which harbor a protease-deficient Omi S276C mutant, exhibited an early onset neurodegeneration and motor abnormalities similar to Parkinson's disease (PD) [9,10] . Missense mutations that lead to a loss of Omi protease activity have been associated with PD [11,12] . These studies suggest that intact Omi protease activity is necessary for neuronal function and survival.…”
Section: Introductionmentioning
confidence: 99%